The influence of community ecological intelligence on mangrove forest preservation - A. Achyani; Suharno Zen; Agus Sujarwanta; Agus Sutanto (University of Muhammadiyah Malang, 2025)
Mangrove forests play a crucial ecological role in coastal protection, biodiversity maintenance, and carbon sequestration. However, their sustainability is increasingly threatened by human activities and environmental degradation. This study aims to investigate the impact of community ecological intelligence (CEI) on the long-term survival of mangrove forests in Labuhan Maringgai District, East Lampung Regency, Lampung Province. The research sample consisted of 174 participants from Sriminosari Village. The study employed a 2x4 factorial design, focusing on the relationship between four levels of CEI and two types of practices related to mangrove conservation. Data was collected using a 20-item questionnaire, rated on a 1-5 scale, to assess participants' knowledge, attitudes, and behaviors towards mangrove conservation. The data were analyzed using Analysis of Variance (ANOVA) followed by Tukey post-hoc tests, and prerequisite tests were conducted to ensure the reliability of the results. The findings revealed that CEI significantly influenced mangrove conservation efforts, with higher CEI levels associated with better conservation outcomes. However, the type of practice did not significantly affect the results, and there was no significant interaction between CEI and practice. This study concludes that CEI